2017
DOI: 10.1039/c7lc00465f
|View full text |Cite|
|
Sign up to set email alerts
|

Automated and controlled mechanical stimulation and functional imaging in vivo in C. elegans

Abstract: A new automated microfluidic platform can deliver a wide range of mechanical stimuli for functional neural imaging in C. elegans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
89
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(93 citation statements)
references
References 60 publications
4
89
0
Order By: Relevance
“…To study touch sensitivity of C. elegans larvae, Cho et al (2018) presented a device adapted from previous devices for studying adult worms (Cho et al, 2017; Nekimken, Fehlauer, et al, 2017), with a fluorescent calcium sensor, GCaMP (Chen et al, 2013), as a readout for neuron activation. To mechanically stimulate a worm, the authors used actuators similar to those described in Section 3, but required a different polymer formulation, resulting in a lower modulus of elasticity to enable actuation suitable for small larvae.…”
Section: Microfluidics For Mechanobiology Of Model Organismsmentioning
confidence: 99%
See 2 more Smart Citations
“…To study touch sensitivity of C. elegans larvae, Cho et al (2018) presented a device adapted from previous devices for studying adult worms (Cho et al, 2017; Nekimken, Fehlauer, et al, 2017), with a fluorescent calcium sensor, GCaMP (Chen et al, 2013), as a readout for neuron activation. To mechanically stimulate a worm, the authors used actuators similar to those described in Section 3, but required a different polymer formulation, resulting in a lower modulus of elasticity to enable actuation suitable for small larvae.…”
Section: Microfluidics For Mechanobiology Of Model Organismsmentioning
confidence: 99%
“…Nekimken, Fehlauer, et al (2017) and Cho et al (2017) used similar lateral pneumatic actuators for stimulation and a fluorescent calcium sensor, GCaMP (Chen et al, 2013), for readout of neuronal activity. With our device, which is described in Section 4, we found that the touch receptor neurons were also activated with a blue light stimulus, such as the excitation light for green fluorescent proteins.…”
Section: Microfluidics For Mechanobiology Of Model Organismsmentioning
confidence: 99%
See 1 more Smart Citation
“…This method has been used to explore the biomechanical properties of the worm’s body 18 and their effects on touch sensitivity 19 , and to develop a biophysical model of mechanotransduction in the touch cells 20 . Another approach is to immobilize a single worm with glue 9 or a microfluidic trap 21,22 and use a glass probe or pneumatic indenter to apply direct stimulus while monitoring calcium transients or electrophysiological activity 23 . However, no method to date has combined the application of a localized, tunable, mechanical stimulus with behavioral recording of the responses of many worms at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…From optogenetic dissection studies, TRN activation is known to be sufficient to activate such behaviors: stimulation of the three anterior neurons (ALML, ALMR, and AVM) causes forward-moving animals to reverse direction, while stimulation of two posterior neurons (PLML and PLMR) results in a speed-up 8 . A third posterior neuron, PVM, is activated via mechanical stimulation [9][10][11] but is not required for behavioral responses to gentle touch 6,7 . Thus, five of the six TRNs are necessary and sufficient to produce touch-evoked avoidance behaviors in adult hermaphrodites.…”
Section: Introductionmentioning
confidence: 99%